A rare case of complete Vogt-Koyanagi-Harada disease presenting to a tertiary care hospital in late stage: Clinical features, diagnosis, and management (Indian Journal of Case Reports, 2021)
Vogt-Koyanagi-Harada disease (VKHD) is a rare T-cell-mediated multisystemic autoimmune disorder affecting organs with high melanocytic concentrations such as uvea, skin, ear, and meninges. VKHD is difficult to diagnose because its clinical presentation is variable and multisystemic which often leads to late diagnosis and treatment allowing the appearance and progression of the disease sequelae. Here, we report the case of a young adult female who was previously undiagnosed and inadequately treated at multiple centers presenting to our hospital in the late stage of VKHD with panuveitis, retinal detachment, hearing loss, alopecia, and vitiligo, which was classified as complete VKH disease and successfully treated in our hospital.